2011
DOI: 10.2341/10-346-l
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Detection and Treatment of Occlusal Caries Using the International Caries Detection and Assessment System

Abstract: Clinical Relevance Occlusal caries is the predominant form of dental caries at the present time. This study documents the variability in detection and treatment of occlusal caries among dentists graduating from different dental schools around the world and practicing in Kuwait. Furthermore, it shows that dentists tend to overtreat occlusal caries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
3
7
1
1
Order By: Relevance
“…The findings from this study confirmed the variability found among dentists in the literature regarding the visual diagnosis of caries. While some studies have shown no effect for the examiner's experience on the accuracy of caries diagnosis , others suggested a possible caries diagnostic disparities among examining investigators . Five different investigators in this study from different specialties and with a minimum of 5 years' experience participated in caries diagnosis.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The findings from this study confirmed the variability found among dentists in the literature regarding the visual diagnosis of caries. While some studies have shown no effect for the examiner's experience on the accuracy of caries diagnosis , others suggested a possible caries diagnostic disparities among examining investigators . Five different investigators in this study from different specialties and with a minimum of 5 years' experience participated in caries diagnosis.…”
Section: Discussionmentioning
confidence: 79%
“…It was interesting to see that when there were no differences in intra-examiner's weighted kappa scores over time, a noteworthy drop in the interexaminer's kappa for some investigators at the 3-month interval was evident. This could be due to the fact that interpretation of ICDAS scoring system is susceptible to investigators subjectivity/bias, clinical experiences and practices, and the individual's decision-making process (3,4,12,13,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…However, caries diagnostic decisions as well as decisions about when to intervene vary considerably among dental practitioners. A tendency to overestimate the presence and depth of caries lesions as well as to treat enamel lesions invasively has been reported [Gordan et al, 2010;Al-Khatrash et al, 2011], particularly when several diagnostic tools were employed. Along with slight or no improvement in the percentage of correctly diagnosed sites, a drastic effect on the selection of treatment options, most commonly invasive interventions, was observed [Pereira et al, 2009;Baelum et al, 2012].…”
Section: Challenges In Diagnosing and Managing Non-cavitated Occlusalmentioning
confidence: 99%
“…Visual description attributed to the scores of the methods used in the study. The scores were recodified in accordance with the presence of caries and without caries = 0 (ICDAS, DR, µ-CT, and Histologic Specimen = 0) and with caries = 1 (ICDAS ≥ 1 and ≤ 6 and DR, µ-CT and Histologic Specimen ≥ 1 and ≤ 4) and in accordance with the localization of the caries and without caries = 0 (ICDAS, DR, µ-CT and Histologic Specimen = 0); with caries in enamel = 1 (ICDAS ≥ 1 and ≤ 3 and DR, µ-CT and Histologic Specimen = 1) and with caries in dentin = 2 (ICDAS ≥ 4 and ≤ 6 and DR, µ-CT and Histologic Specimen ≥ 2 and ≤ 4) (Al-Khatrash et al, 2011). In cases of disagreement among the examiners about the number of the score, the criterion of consensus was adopted to determine the score of the tooth for each method.…”
Section: Scoresmentioning
confidence: 69%